Domestic Trade Impacts of the Expansion of the National Expressway Network in China - World Bank (Washington, DC, 2014)
China's outstanding achievements in economic growth and poverty reduction over the last fifteen years have been well documented. A major element of that growth consisted of the development of its infrastructure, particularly transport. All modes of transport have seen their networks expanded, to provide the infrastructure needed to support the broader development goals. Among the surface modes (excluding pipelines or waterways), road transport has seen its share grow from 45 percent to 60 percent in terms of passenger-km and from 24 percent to 30 percent in terms of freight ton-km. From 1990 to 2005, during the period of the 8th, 9th and 10th Five-Year Plans, China completed nearly 41,000 km of high-grade tolled expressways comprising the national trunk highway system (NTHS), or as it is now called, the national expressway network (NEN). During this period approximately 400,000 km of local and township roads were also improved. This was achieved by investing upwards of US$40 billion per year, with about one third of that amount allocated to development of the NEN. Behind this overall strategy, the expressway plan seeks to connect all cities with more than 200,000 people, serving as facilitator of economic and social interactions as the economy comes to rely more and more on road transport. In prioritizing the selection of cities (nodes) to be connected, the planning process has incorporated economic and transport objectives (including trade and container traffic requirements, and tourism needs), giving special consideration to poorer regions and environmental issues. This will improve the regional integration of the economy and allow growth dynamics to expand from the coastal regions to the interior and western parts of the country.